If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -80x + -81 = x + -1(-3) Reorder the terms: -81 + -80x = x + -1(-3) Multiply -1 * -3 -81 + -80x = x + 3 Reorder the terms: -81 + -80x = 3 + x Solving -81 + -80x = 3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -81 + -80x + -1x = 3 + x + -1x Combine like terms: -80x + -1x = -81x -81 + -81x = 3 + x + -1x Combine like terms: x + -1x = 0 -81 + -81x = 3 + 0 -81 + -81x = 3 Add '81' to each side of the equation. -81 + 81 + -81x = 3 + 81 Combine like terms: -81 + 81 = 0 0 + -81x = 3 + 81 -81x = 3 + 81 Combine like terms: 3 + 81 = 84 -81x = 84 Divide each side by '-81'. x = -1.037037037 Simplifying x = -1.037037037
| 7x-5+16+x=11x-x-3 | | -9z-9=81 | | 7-8p=71 | | ln(4t)=2.3 | | -32x^2+56-12=0 | | 5(-2x+3)=45 | | f(x)=-9x+8 | | 7x+y+3z=20 | | 5x-3y+2z=3 | | 99=5c+6c | | 99=5c | | -13+z=17 | | -7a-6a=65 | | -12-2k=-2k-13k-13 | | T/3.6= | | 16-5y=51 | | -4x+13-4x+x=-8 | | lny=-4 | | 2(x^2+9)=5(x^2-23)+x^2+33 | | x-2/4x^5-58x | | -6(v-6)=-24 | | 5x-3y+2z=y | | p=q+7 | | -7/8t=5/4 | | 56/-10 | | 54=6-6u | | 81a^2+90a+k= | | -6x-12=36 | | 2x-5(x-5)=-2+4x-8 | | x^2+y^2+z^2-z=0 | | -36+24=-7x+13x | | f(x)=-7x^2-14x-6 |